Finding new agents in medicinal plants to act on the myometrium. Issue 3 (2nd January 2014) - Kupittayanant, Sajeera; Munglue, Phukphon; Lijuan, Wanwisa; Promprom, Wilawan; Budhaklala, Nopparat; Wray, Susan
<x xml:space="preserve">Abstract</x> New Findings What is the topic of this review? How do medicinal plants act on the myometrium? What are the underlying mechanisms whereby medicinal plants exert their effects? What advances does it highlight? We show that medicinal plants can affect uterine contraction at many loci. These studies give us a better understanding of how medicinal plants work on the uterus and can be applied in other areas of smooth muscle physiology, as well as pharmacy and medicine. This knowledge is also useful for developing new agents with potential to improve women's reproductive and gynaecological heath. This report summarizes work investigating the effects of some medicinal plants on uterine contraction. As there is a clinical need to find better drugs to help control uterine activity, and novel compounds are sought, the mechanisms whereby the medicinal plants exert their effects, as well as their major compounds, are discussed. By identifying the plants, major constituents and mechanisms, this review also illustrates the potential for development of new drugs, so that better ways to treat uterine disorders will be available to women worldwide.